Analysis of Banana Production Practices and Constraints in Embu County, Kenya - Muthee, Arphaxard Ireri; Gichimu, Bernard Mukiri; Nthakanio , Paul Njiruh (Asian Journal of Agriculture and Rural Development, 2019)
This study was carried out to determine banana production constraints in Embu County in order to seal this production gap. A survey was conducted in the four sub-counties in Embu County namely, Runyenjes, Manyatta, Mbeere North and Mbeere South, to assess the production constraints limiting banana production. Respondents were smallholder banana farmers selected using cluster sampling method from 22 farmers’ groups in the County. The cluster sampling was based on a number of operational irrigation schemes in each of the four sub-counties, and with at least 15 – 30 active members. The study established that banana production in Embu County is highly constrained by poor husbandry practices, pests and diseases, lack of clean planting materials, and lack of adequate extension services.